Modificação da argila montmorilonita e do carvão de coco de babaçu ativado com óxido de ferro: caracterização e aplicação na adsorção do azul de metileno - Cottet, Leila (2010)
The montmorillonite clay and babassu coconut activated carbon have been modified, characterized and applied in the study of methylene blue dye adsorption. In the modification the precipitation method (ex-situ) was used. The two modified adsorbents showed magnetic characteristics and can be used in the magnetic separation. The analyses by scanning electron microscopy, energy dispersive X-ray and fourier transform infrared (FTIR) spectroscope in both adsorbents suggested that the main magnetic phase formed was magnetite. The surface area of modified clay was 118.1m²g?¹ and the modified activated carbon was 160.4 m²g?¹. The surface charge of the two materials was positive at pH 5.5. In kinetics, the results showed better adjustment to the model of pseudo-second order model. In the equilibrium study, the results showed better adjustment to Langmuir model. A rise in the system temperature resulted in an increase in the amount adsorbed. Calculated thermodynamic parameters indicated non-spontaneous systems (?Go), endothermic (?Ho). Activation energy values were 19.21 kJ moL?¹ and -14.65 kJ moL?¹ for the modified clay and the modified activated carbon, respectively, indicating a process of physical nature. With the increase in the initial dye concentration there was an increase of the amount adsorbed and a decrease in the removal percentage.